1992
DOI: 10.1172/jci115937
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic effects of L-arginine in the hypercholesterolemic rabbit.

Abstract: The purpose of this study was to determine if chronic administration of L-arginine, the precursor of endothelium-derived relaxing factor (EDRF), normalizes endothelium-dependent relaxation and decreases atherosclerosis in hypercholesterolemic animals. Male rabbits were fed (a) normal rabbit chow; (b) 1% cholesterol diet; or (c) 1% cholesterol diet supplemented by 2.25% L-arginine HCI in drinking water. Arginine supplementation doubled plasma arginine levels without affecting serum cholesterol values. After 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
267
0
14

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 661 publications
(302 citation statements)
references
References 31 publications
21
267
0
14
Order By: Relevance
“…Several groups demonstrated that acute and chronic supplementation of L-arginine improves endothelial vasodilator responses in cholesterol fed animals and in patients with hypercholesterolemia and atherosclerosis [20][21][22][23]. Following these early studies, numerous studies with supplemental Larginine therapy have been conducted in animal models and in humans; however, no consistent results can be achieved [24••].…”
Section: Controversy Of L-arginine Supplemental Therapy In Atherosclementioning
confidence: 99%
“…Several groups demonstrated that acute and chronic supplementation of L-arginine improves endothelial vasodilator responses in cholesterol fed animals and in patients with hypercholesterolemia and atherosclerosis [20][21][22][23]. Following these early studies, numerous studies with supplemental Larginine therapy have been conducted in animal models and in humans; however, no consistent results can be achieved [24••].…”
Section: Controversy Of L-arginine Supplemental Therapy In Atherosclementioning
confidence: 99%
“…Supplementation with 2.25% L-arginine HO in the drinking water results in a sixfold enrichment of this amino acid (based on the daily average water and food intake of the animals) and induces a twofold increase in plasma arginine levels. 14 To determine if any effects of L-arginine supplementation were mediated by changes in caloric or nitrogen balance, a fourth group received a 1% cholesterol diet supplemented with 0.9% L-methionine (Met) in the drinking water to induce a sixfold increase in the daily intake of this amino acid.…”
Section: Animalsmentioning
confidence: 99%
“…14 To determine if this antiatherogenic effect of L-arginine doubled in the Arg group. There was no difference in maximum aggregation initiated by ADP (100 ^mol/L) between washed platelets from Con, Met, and Choi animals, but aggregation of platelets from Arg animals was significantly decreased (/ J <.05).…”
mentioning
confidence: 99%
“…A reduction in vascular availability of nitric oxide determines damage to endothelium-dependent vasodilatation, an increased tendency for platelet aggregation and adhesion of monocytes to the endothelium, and influences the proliferation of vascular smooth muscle cells, probably contributing to the onset and progression of atherosclerosis. In animal models of hypercholesterolemia, pharmacological inhibition of nitric oxide synthesis accelerates atherosclerosis 53 , but increased availability of nitric oxide decreases and may even lead to the regression of the disease 54,55 .…”
Section: Caramori and Zago Endothelial Dysfunction And Coronary Artermentioning
confidence: 99%